The influence of the war situation on the mental states of the population of Ukraine and their art-therapeutic psychocorrection - Shopsha, Mykola; Shopsha, Olena; Zhyvaho, Khrystyna; Fesenyuk, Natalia; Koliadenko, Nina; Bachurina, Nadiia (My University, 2023)
The relevance of studying mental states is related to their direct impact on the quality of human life, which makes it important to clarify the impact of prolonged war stress on mental states, develop appropriate psychocorrectional training methods, and determine their effectiveness. Актуальність дослідження психічних станів пов’язана з їхнім безпосереднім впливом на якість життя людини, що обумовлює важливість з’ясування впливу тривалого воєнного стресу на психічні стани, розробки відповідних психокорекційних тренінгових методик і визначення їх ефективності.
Keywords: psychodiagnostics; психокорекція; psychocorrection; psychocorrection; воєнна медицина; military medicine